Hospital Information Management Using Open Source Software: Results of the MIDA Project in 3 Hospitals in Rwanda - Karara, Gustave; Verbeke, Frank; Nyssen, Marc (Journal of Health Informatics in Africa, 2013)
Background and Purpose: The health sector in many developing countries, especially in sub-Saharan Africa, suffers since a long time from poor health information collection and analysis systems. This study evaluates the results of 3 projects financed by the Migration for Development in Africa-Great Lakes (MIDA GL) program in 3 Rwandan hospitals: Kigali University Teaching Hospital (CHUK), Neuro-psychiatric hospital Caraës-Ndera (NPH-CN) and Gihundwe district hospital (GDH). These projects aimed to empower hospital staff in collecting and analyzing hospital information by using OpenClinic, an open source hospital information management system. Methods: The first analysis at CHUK used the results of a CAP (competence, ability, practice) survey addressed to healthcare staff in using OpenClinic, in 2010 and 2012. The second method analyzed results of NPH-CN and GDH in the OpenClinic software utilization between 1/1/2011 and 31/12/2012. Results: Results showed that routine OpenClinic utilization increased by 20% (from 36.0% to 56.3%) at CHUK between 2010 and 2012 and skills levels increased significantly in admission (+9.2%) and laboratory (+10.0%) departments where the training programs were run. The results obtained from the hospitals of Gihundwe and Ndera showed that the 2 hospitals almost doubled their income one year after implementation and indicators like case load, encounter load and numbers of provided health care deliveries continue to increase linearly, demonstrating the continuity of OpenClinic utilization. Clinical modules however have not yet been well adopted in Ndera and Gihundwe: reason for encounter documentation and diagnostic coding are not being performed systematically. Conclusion: The MIDA GL funding allowed 3 Rwandan hospitals to implement the OpenClinic tool easily and to improve its utilization by gathering and centralization of health information in real-time. The improvement of user skills level in OpenClinic enabled them to take ownership of the tool proving the need for regular staff training and evaluations in the OpenClinic utilization. Keywords: MIDA, Empowering healthcare staff, OpenClinic utilization, Hospital information system, Rwanda